Romans - Hahn, Scott, 1957- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2017)
In this addition to the successful Catholic Commentary on Sacred Scripture (CCSS) series, Scott Hahn, a bestselling author and a leading Catholic interpreter of Scripture, examines Romans from within the living tradition of the Church for pastoral ministers, lay readers, and students alike. The CCSS relates Scripture to Christian life today, is faithfully Catholic, and is supplemented by features designed to help readers understand the Bible more deeply and use it more effectively in teaching, preaching, evangelization, and other forms of ministry. Supported by leading Catholic scholars as well as popular Bible teachers, the series offers a unique level of commentary for Catholic students of the Bible. Its attractive packaging and accessible writing style make it a series to own--and to read! Drawn from the best of contemporary scholarship, series volumes are keyed to the liturgical year and include an index of pastoral subjects.
Bibliografia.
Keywords: Biblia. -- Commenti